2015
DOI: 10.1080/08927014.2014.996143
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and pathogenicity ofCandida albicansis enhanced in biofilms containing oral bacteria

Abstract: This study examined the influence of bacteria on the virulence and pathogenicity of candidal biofilms. Mature biofilms (Candida albicans-only, bacteria-only, C. albicans with bacteria) were generated on acrylic and either analysed directly, or used to infect a reconstituted human oral epithelium (RHOE). Analyses included Candida hyphae enumeration and assessment of Candida virulence gene expression. Lactate dehydrogenase (LDH) activity and Candida tissue invasion following biofilm infection of the RHOE were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 46 publications
5
76
2
1
Order By: Relevance
“…Similar enhancement of fungal burden and invasion is seen in murine C. albicans-bacterial coinfection and epithelial disease models (56)(57)(58)(59)(60).…”
Section: Discussionsupporting
confidence: 49%
“…Similar enhancement of fungal burden and invasion is seen in murine C. albicans-bacterial coinfection and epithelial disease models (56)(57)(58)(59)(60).…”
Section: Discussionsupporting
confidence: 49%
“…It has also been demonstrated that glycosyltransferase B from S. mutans-upregulated genes are involved with morphogenesis and adhesion (HWP1, ALS1, and ALS3) of C. albicans [Ellepola et al, 2017]. In mono-species biofilms of C. albicans, morphogenesis is probably due to neutral pH, whilst morphogenesis observed in dual-species biofilms may be related to sugar starvation and direct bacterial interaction [Morales and Hogan, 2010;Diaz et al, 2012;Cavalcanti et al, 2015]. The activation of morphogenesis in dual-species biofilms may favor the adhesion of C. albicans, as well as promote a greater cell-wall surface for interaction with S. mutans cells.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms render the organisms resistant to antimicrobial agents and protect them from immune cells (1315). Moreover, fungal filamentation is a known Candida virulence factor that damages host tissues and triggers specific host immune responses (1619). Distinct interspecies interactions in this biofilm environment were clearly evident, where E. coli tended to be closely associated with the fungal cell walls, while S. marcescens used its fimbriae to form a “bridge” between C. tropicalis and E. coli that stabilized the bacterium-fungus biofilm structure.…”
Section: Commentarymentioning
confidence: 99%